2022
DOI: 10.1111/mec.16588
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide transcriptomic changes reveal the genetic pathways involved in insect migration

Abstract: Insects are capable of extraordinary feats of long-distance movement that have profound impacts on the function of terrestrial ecosystems. The ability to undertake these movements arose multiple times through the evolution of a suite of traits that make up the migratory syndrome, however the underlying genetic pathways involved remain poorly understood. Migratory hoverflies (Diptera: Syrphidae) are an emerging model group for studies of migration. They undertake seasonal movements in huge numbers across large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 187 publications
0
8
0
Order By: Relevance
“…Hence, we wrongly predicted some level of IBD within study areas because our study species are not migratory. Given the high prevalence of hoverfly species presenting a partial migration syndrome (Doyle et al, 2022; Menz et al, 2019; Speight, 2017), the genetic and structural pathways to efficient dispersal might also be present in nonmigratory hoverflies such as SP and MF. Indeed, even rare nonmigratory species may fly several kilometers away from their emergence sites (Rotheray et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we wrongly predicted some level of IBD within study areas because our study species are not migratory. Given the high prevalence of hoverfly species presenting a partial migration syndrome (Doyle et al, 2022; Menz et al, 2019; Speight, 2017), the genetic and structural pathways to efficient dispersal might also be present in nonmigratory hoverflies such as SP and MF. Indeed, even rare nonmigratory species may fly several kilometers away from their emergence sites (Rotheray et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For other eight species, we downloaded GTF and genome FASTA files from Ensembl Metazoa [https://metazoa.ensembl.org/]: sea urchin ( Strongylocentrotus purpuratus: Spu: Spur_5.0 v51), fruit fly ( Drosophila melanogaster, Dme : dm6, v26), yellow fever mosquito ( Aedes aegypti, Aae : AaegL5, v46), domestic silk moth ( Bombyx mori, Bmo : ASM15162v1, v45), red flour beetle ( Tribolium castaneum, Tca : Tcas5.2, v45), honey bee ( Apis mellifera, Ame : Amel_4.5, v35), centipede ( Strigamia maritima , Sma: Smar1, v26), California two-spot octopus ( Octopus bimaculoides, Obi : ASM119413v2). For other three species, we used the GTF and genome FASTA files from the relative publications: amphioxus ( Branchiostoma lanceolatum , Bla: 54 ), marmalade hoverfly ( Episyrphus balteatus , Eba: 55 ), mayfly ( Cloeon dipterum , Cdi: 12 ). For the cockroach ( Blattella germanica , Bge) we downloaded the GFF3 (blager_OGSv1.2.1.gff3) and the genome FASTA (GCA_000762945.2_Bger_2.0_genomic.fna.gz) from https://i5k.nal.usda.gov/content/data-downloads.…”
Section: Methodsmentioning
confidence: 99%
“…The fezzik ( fiz ) gene is located on the X chromosome and its expression has been shown to affect a variety of traits, including larval growth rate, body size determination, cold and insecticide tolerance (Glaser‐Schmitt & Parsch, 2018). In a study using replicate experimental populations of D. melanogaster , fiz was strongly down‐regulated in populations adapted to larval malnutrition (Kawecki et al, 2021); while another study detected its orthologue as highly up‐regulated in actively migrating Episyrphus balteatus in comparison to the non‐migratory summer morph (Doyle et al, 2022). The fiz protein shows evidence for adaptive protein evolution since D. melanogaster 's divergence from D. simulans (Langley et al, 2012; Saminadin‐Peter et al, 2012), with fiz ranked among the top candidates for adaptive evolution on the D. melanogaster lineage (Langley et al, 2012).…”
Section: The Fezzik Gene: a Case Studymentioning
confidence: 99%
“…In line with this observation, previous work found that fiz expression affects adult starvation resistance in a sex‐specific manner, and that in the genetic background of a natural population, variation at SNP67 has a stronger effect in females than in males (Glaser‐Schmitt et al, 2021), suggesting that adult starvation resistance may be the phenotype under selection. However, it is possible that a combination of it and/or other traits that fiz expression has been proposed or demonstrated to affect (see Glaser‐Schmitt & Parsch, 2018; Kawecki et al, 2021; Doyle et al, 2022 for examples) are the target(s) of selection. Similarly, it is important to note that there are many factors relevant to selection in nature that are not accounted for in the models we considered.…”
Section: The Fezzik Gene: a Case Studymentioning
confidence: 99%
See 1 more Smart Citation